Yttrium speciation in sulfate-rich hydrothermal ore-forming fluids. (15th May 2022) - Guan, Qiushi; Mei, Yuan; Etschmann, Barbara; Louvel, Marion; Testemale, Denis; Bastrakov, Evgeniy; Brugger, Joël
Abstract: Rare Earth elements (REE) are gaining importance due to their increasing industrial applications and usefulness as petrogenetic indicators. REE-sulfate complexes are some of the most stable REE aqueous species in hydrothermal fluids, and may be responsible for REE transport and deposition in a wide variety of geological environments, ranging from sedimentary basins to magmatic hydrothermal settings. However, the thermodynamic properties of most REE-sulfate complexes are derived from extrapolation of ambient temperature data, since direct information on REE-sulfate complexing under hydrothermal conditions is only available for Nd, Sm and Er to 250 °C (Migdisov and William-Jones, 2008, 2016). We employed ab initio molecular dynamics (MD) simulations to calculate the speciation and thermodynamic properties of yttrium(III) in sulfate and sulfate-chloride solutions at temperatures and pressures up to 500 °C and 800 bar. The MD results were complemented by in situ X-Ray Absorption Spectroscopy (XAS) measurements. Both MD and XAS show that yttrium(III) sulfate complexes form and become increasingly stable with increasing temperature (≥200 °C). The MD results also suggest that mixed yttrium-sulfate-chloride complexes (that cannot be distinguished from mixtures of chloride and sulfate complexes in XAS experiments) form at ≥ 350 °C. Two structures with two different Y(III)-S distances (monodentate and bidentate) are observed for Y(III)-sulfate bonding. The formation constants, derived via thermodynamic integration, for the Y(III) mono- and di-sulfate complexes parallel the trends for those of Nd, Sm and Er determined experimentally to 250 °C. The derived formation constants were used to fit revised Helgeson-Kirkham-Flowers equation-of-state parameters that enabled calculation of formation constants for Y(SO4 ) + and Y(SO4 )2 − over a wide range of temperatures and pressures. The presence of sulfate increases the solubility of Y(III) under specific conditions. Since the stability of sulfate is redox sensitive, Y(III) solubility becomes highly redox-sensitive, with rapid precipitation of Y minerals upon destabilisation of aqueous sulfate.